Forage yield and quality in elephant grass cv. Pioneiro harvested at different cutting height sand times - Figueira, Danúbia Nogueira [UNESP]; Neumann, Mikael; Ueno, Robson Kyoshi; Galbeiro, Sandra; Bueno, Antônio Vinícius Iank (Universidade Estadual de Londrina, 2016)
This study aimed to evaluate the effect of cutting height and harvest time on forage yield and quality in elephant grass (Pennisetum purpureum Schum.) cv. Pioneiro. Experimental plots were arranged in a randomized block split-plot design. The treatments consisted of four residual heights (30, 40, 50, and 60 cm)and three successive harvest times (January, March, and May 2011). There was a significant interaction between residual height and harvest time for the proportion of stems (P<0.05) and leaves (P<0.01) in the forage. A similar result was observed for fresh (P<0.01) and dry (P<0.01) forage yield at the first and third harvests. There was a quadratic relationship between dry forage yield and residual height, with a maximum yield of 5738 kg ha-1 ataresidual height of 50.17 cm in the second harvest. The increase in residual height from 30 to 60 cm, regardless of harvest time, reduced neutral detergent fiber (NDF)and acid detergent fiber (ADF) and increased crude protein content. Forage yield and quality were highest at 40-50 cm residual heights.
Keywords: Acid detergent fiber; Crude protein; Forage components; Forage yield; Neutral detergent fiber